Neglected Tropical Diseases (NTDs) - A Snapshot of Research - Paul, Partha; Podder, Dipu; Kumar, Arup; Rahman, Md. Ataur; Rahman, Md. Hajbiur; Purba, Nafisa Habib; Al Hasan, Md. Zahid; Akter, Tabassum (Recent Research in Science and Technology, 2021)
More than a billion people-one-sixth of the earth’s population is infected with one or more neglected tropical diseases (NTDs) in developing countries. Over the past decade, interests in NTDs have resurged as these are a barrier to achieving broader human development outcomes (e.g., improved newborn, child and maternal health, food, and nutritional safety). Several national and international organizations (such as the WHO, USAID, CDC, and others) concentrate on NTDs and fighting to control or prevent them. This review describes a brief introduction to NTDs, the global burden of the diseases in terms of disability-adjusted life years (DALYs), years lived with disability (YLDs) and years of life lost (YLLs). This paper also reviews the negative impact of these diseases on global economies and discusses strategies for public health to prevent and eliminate these diseases, the achievements and challenges that can be achieved to address adversity there.